The Effectiveness of Instilling Students’ Discipline for Criminology Students: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Criminology has become in-demand in schools and universities, not because of the bearingappearance that attracts the youth to enroll in, but because of the moral attitude and otherforms of showing respect to their other upper-class men and professors. The variety ofopportunities that await after the accomplishment of the degree. The criminology departmenthas its own rules and regulations that must followed, such as giving respect, hand gestures,salutes, sidestepping, and proper greetings to their upper-class men and professors; theymust obey the command as their job as cadets, as well as proper haircut and uniform. Somestudents violate this, thinking they forgot or they cannot recognize their seniors; they ought tofollow orders while studying, and they will carry on until they have a profession. The usualproblem is the discipline of criminology student starts with their respective homes. Theenvironment plays a huge role in criminology students’ behavior and attitude. It shows in howthey were their uniform, proper haircut, and also their behavior when wearing their uniform.The result reveals that the greatest number of respondents were both in 2nd year and 3rdyear, and the lowest number of respondents were faculty members. The result showed thatthe respondents had agreed that they could adopt unusual traditions, adjust uncommonpractices, and instruct new apprentices in terms of culture, as evidenced by the overallweighted mean rating of 2.91.Researchers concluded that there is a split belief between male and female respondentsabout instilling students’ discipline for criminology students regardless of their school year.However, their age and experience might cause them to have different views on the matterwith regard to problems encountered; moreover, in different cultures, different practices arenot a concern as long as the student is willing to adapt to new changes.
Keywords: Criminology